2021
DOI: 10.1186/s13578-021-00713-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neutralizing antibody response to COVID-19 mRNA vaccines in cancer patients

Abstract: There is currently a critical need to determine the efficacy of SARS-CoV-2 vaccination for immunocompromised patients. In this study, we determined the neutralizing antibody response in 160 cancer patients diagnosed with chronic lymphocytic leukemia (CLL), lung cancer, breast cancer, and various non-Hodgkin’s lymphomas (NHL), after they received two doses of mRNA vaccines. Serum from 46 mRNA vaccinated health care workers (HCWs) served as healthy controls. We discovered that (1) cancer patients exhibited reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 12 publications
10
39
0
Order By: Relevance
“…This corroborated our previous findings in hematological cancer patients on similar B-cell depleting therapies. [ 17 ] Other studies have shown similar correlations between vaccine induced antibody levels and the time since last dose of anti-CD20 therapy. [ 18 ] Consistent with these observations, circulating CD20 cell levels also correlate with vaccine-induced antibody responses.…”
Section: Discussionmentioning
confidence: 80%
“…This corroborated our previous findings in hematological cancer patients on similar B-cell depleting therapies. [ 17 ] Other studies have shown similar correlations between vaccine induced antibody levels and the time since last dose of anti-CD20 therapy. [ 18 ] Consistent with these observations, circulating CD20 cell levels also correlate with vaccine-induced antibody responses.…”
Section: Discussionmentioning
confidence: 80%
“…However, the ability of mRNA-based SARS-CoV-2 vaccines to immunize primary or treatment-induced immunocompromised individuals has recently been questioned (Collier et al, 2021). In particular, patients with inflammatory bowel disease under infliximab treatment (Kennedy et al, 2021), patients who have received an allogeneic stem cell transplantation (Lafarge et al, 2022), cancer patients (Chung et al, 2021;Ribas et al, 2021;Zeng et al, 2021;Greenberger et al, 2021aGreenberger et al, , 2021bThakkar et al, 2021aThakkar et al, , 2021b, methotrexate treatment (Mahil et al, 2021), kidney transplant or hemodialysis (Bachelet et al, 2021;Danthu et al, 2021), or multiple sclerosis (Apostolidis et al, 2021) have all demonstrated a reduced ability to mount an immune response, potentially adversely affecting protection offered by vaccines. However, studies in which a comprehensive comparative analysis of both humoral and cellular immune responses after a third dose of vaccine is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the immunocompromised state of patients with leukemia, a combination of disease and immunosuppressive therapies, has raised questions regarding the effectiveness of COVID-19 vaccines among people with leukemia [ 6 , 29 – 31 ]. Some of the strongest evidence regarding reduced antibody formation from COVID-19 relate to B-cell-depleting therapies, such as anti-CD20 monoclonal antibodies (e.g., rituximab, ofatumumab, obinutuzumab) [ 29 , 32 , 33 ]. Specifically, Zeng et al, using a study population comprised of patients with cancer and non-cancer control health care workers (HCW), demonstrated CLL demonstrated a lower mean antibody response than solid tumors and HCW controls; in comparing patients with CLL who were not prescribed B-cell-depleting therapy, B-cell-depleting therapy use was associated with lower mean antibody levels [ 32 ].…”
Section: Prevention and Management Of Covid-19 In Leukemia Patientsmentioning
confidence: 99%